Dietary supplements and multiple sclerosis : a health professional's guide - Bowling, Allen C. (Demos, 2004)
There is a relatively high use of complementary and alternative medicine (CAM), especially dietary supplements, among people with multiple sclerosis (MS). Health professionals with CAM information can improve the quality of patient care by guiding patients away from possibly harmful therapies and, if appropriate, towards low-risk, possibly effective therapies. Dietary Supplements and Multiple Sclerosis is meant to be referred to when people with MS ask a question about a particular dietary supplement. Supplements are arranged in alphabetical order under the most commonly used name. In addition.